Bortezomib for treatment of therapy-refractory anti-NMDA receptor encephalitis. (24th January 2017) - Scheibe, Franziska; Prüss, Harald; Mengel, Annerose M.; Kohler, Siegfried; Nümann, Astrid; Köhnlein, Martin; Ruprecht, Klemens; Alexander, Tobias; Hiepe, Falk; Meisel, Andreas
Abstract : Objective: We assessed the therapeutic potential of the plasma-cell-depleting proteasome inhibitor bortezomib in severe and therapy-refractory cases of anti–NMDA receptor (anti-NMDAR) encephalitis. Methods: Five severely affected patients with anti-NMDAR encephalitis with delayed treatment response or resistance to standard immunosuppressive and B-cell-depleting drugs (corticosteroids, IV immunoglobulins, plasma exchange, immunoadsorption, rituximab, cyclophosphamide) who required medical treatment and artificial ventilation on intensive care units were treated with 1–6 cycles of 1.3 mg/m 2 bortezomib. Occurrence of adverse events was closely monitored. Results: Bortezomib treatment showed clinical improvement or disease remission, which was accompanied by a partial NMDAR antibody titer decline in 4 of 5 patients. With respect to disease severity, addition of bortezomib to the multimodal immunosuppressive treatment regimen was associated with an acceptable safety profile. Conclusions: Our study identifies bortezomib as a promising escalation therapy for severe and therapy-refractory anti-NMDAR encephalitis. Classification of evidence: This retrospective case series provides Class IV evidence that bortezomib reduces antibody titers and improves the clinical course of patients with severe anti-NMDAR encephalitis.